The impact of growth imbalances in Urban Centre : case study of selected villages on the embankment of Sarawak River - Hasmawati, Sapawi (Universiti Malaysia Sarawak (UNIMAS), 2001)
The study area, a stretch of 7 villagers is situated in the middle of the booming Kuching town center and yet portrays the characteristics of marginalized area- it lacks most of the basic amenities and luxury that comes with the standard urban residential.